Evaluating factors of institutionalization of political parties in Afghanistan : 2001-2014 - Zahir, Shoaib Abdul (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2015)
This study evaluates the factors of political parties' institutionalization in post September 11 Afghanistan. It uses Svåsand-Randall political party institutionalization model as the framework for analysis. It assumes that there is a close link between political stability and political party institutionalization. Therefore, it argues that formal institutional context, conducive environment, capacity of political parties and political will are essential for institutionalization of political parties in Afghanistan. The study used a combination of descriptive and historical analytical methods of data collection and analysis. This study is composed of five chapters. Chapter One provides the essential background information. Chapter Two discusses the socio-political context of political party institutionalization since the early 20th century. Chapter Three describes the Bonn Agreement and the post-Bonn political setup. Chapter Four examines the factors of political party institutionalization in post September 11 Afghan society. In the final chapter, based on the discussion and data presented in Chapter Four, the findings of the study and valuable recommendations are given. The study, among others, found that political parties in Afghanistan could have a more stabilizing role in the politics and democratizing of the political process in Afghanistan if the political leadership had provided the parties with a conducive environment to operate without restrictions. The leadership had side-lined political parties which prevented their development and institutionalization. The study also found that the complexity of the system of law in Afghanistan, the political constraints, the social perception and the weak organizational capability of political parties have also contributed to the marginalization of parties from the political scene. Finally, this study recommends that democratization efforts in Afghanistan should consider the institutionalization of political parties as a priority. Immediate actions should be taken to simplify the laws and establish the necessary institutional grounds for political parties to operate. Educating the populace on the role of political parties in consolidating democracy will change their perception for good results. Lastly, the political leadership of the country must build its trust on positive participation of political parties in the political process.